Formulasi dan Penentuan Nilai SPF (Sun Protection Factor) Sediaan Lotion Ekstrak Daun Kecombrang (Etlingera Elatior) Secara in Vitro dengan Metode Spektrofotometri Uv-Vis: In Vitro Formulation and Determination of the SPF (Sun Protection Factor) Lotion Preparation of Kecombrang Leaf Extract (Etlingera Elatior) Using Uv-Vis Spectrophotometry Method - Diah Diah; Leli Nurlaeli; Riasa Barata Nian (UIMA Press, 2023)
Indonesia is a tropical country where it is very possible for the skin to continue to be exposed to sunlight. Free radicals in the form of ultraviolet rays from the sun when excess will cause damage to the skin. Prevention of adverse effects due to sun exposure can be done by using sunscreen. One of the most common sunscreen products is lotion. The use of lotions that contain antioxidants can be done to make it easier to protect the skin from exposure to free radicals. One of the plants that has antioxidant activity is kecombrang leaves. The purpose of this study was to determine the SPF (Sun Protection Factor) value of kecombrang leaf extract lotion (Etlingera elatior) using the Uv-vis spectrophotometry method. The results showed that F1, F2 and F3 had SPF values. F3 at a concentration of 800 ppm has the highest SPF value of 18.59 and is included in the ultraprotection category.